Avaliação de prejuizos causados pela mosca-da-azeitona Bactrocera (Daculus) oleae na Ilha Terceira, Açores - Menezes, Carla (2013)
In the Azores archipelago, the olive tree only occurs in 2 Islands, Terceira and Pico. The olive fruit fly, Bactrocera oleae (Gmelin) is the key pest for this crop on the Island of Terceira, by causing important damage. Monitoring of B. oleae adults showed the occurrence of 2 population peaks, one of greater intensity in October and another of lesser intensity, in August. For the assessment of the damage caused by B. oleae, were held, in 2010, samplings of olives in 2 orchards, one with a high number of treatments and the other without any treatment. The intensity of attack in the olives, in the orchard with treatments was just 1% and in the orchard without treatments, was 66% of the olives.